Water, life, and profit : fluid economies and cultures of Niamey, Niger - Keough, Sara Beth, 1976-; Youngstedt, Scott M. (Berghahn Books, 2019)
"Water, Life, and Profit offers a holistic analysis of the people, economies, cultural symbolism, and material culture involved in the management, production, distribution, and consumption of drinking water in the urban context of Niamey, Niger. Paying particular attention to two key groups of people who provide water to most of Niamey's residents - door-to-door water vendors, and those that sell water in one-half liter plastic bags (sachets) on the street or in small shops -, the authors offer new insights into how Niamey's water economies affect gender, ethnicity, class, and spatial structure today"--Provided by publisher.
Keywords: Drinking water -- Niger -- Niamey.; Drinking water -- Economic aspects -- Niger -- Niamey.; Drinking water -- Social aspects -- Niger -- Niamey.; Bottled water industry -- Economic aspects -- Niger -- Niamey.; Bottled water industry -- Social aspects -- Niger -- Niamey.; Eau potable -- Niger -- Niamey.; Eau potable -- Aspect économique -- Niger -- Niamey.; Eau potable -- Aspect social -- Niger -- Niamey.; Eau en bouteille -- Industrie -- Aspect économique -- Niger -- Niamey.; Eau en bouteille -- Industrie -- Aspect social -- Niger -- Niamey.; SOCIAL SCIENCE / Anthropology / Cultural & Social.; SOCIAL SCIENCE / Anthropology / Cultural; Drinking water; Drinking water -- Economic aspects; Niger -- Niamey; Drinking Water.; Water Distribution.; Water Economy.; Water Vendors.; West Africa.